Pirouette: higher-order typed functional choreographies - Hirsch, Andrew K.; Garg, Deepak (Proceedings of ACM on programming languages, 2022)
We present Pirouette, a language for typed higher-order functional choreographic programming. Pirouette offers programmers the ability to write a centralized functional program and compile it via endpoint projection into programs for each node in a distributed system. Moreover, Pirouette is defined generically over a (local) language of messages, and lifts guarantees about the message type system to its own. Message type soundness also guarantees deadlock freedom. All of our results are verified in Coq.